A study on the understanding of parents and the public in child pornography (child sexual abuse) issue and its effect towards children in preschools in Kuching, Sarawak / Aisha Parveen Badron - Badron, Aisha Parveen (Universiti Teknologi MARA, Sarawak, 2017)
In this chapter, Section 1.2 discusses on the background of study, Section 1.3 states the problem statements of my research, Section 1.4 states my research objectives, Section 1.5 states my research questions, Section 1.6 states the scope of my study, Section 1.7 explains briefly the significance of why this study should be conducted and lastly Section 1.8 discusses the operational definition of various key terms in our research and 1.9 is the summary of the chapter.